Congenital hypothyroidism in Calabria: epidemiological and clinical aspects - Mariangiola Baserga; Maria Novella Pullano (Istituto Superiore di Sanità, 2009)
Neonatal screening of congenital hypothyroidism (CH), carried out on all newborns 3rd -5th day of life, has a very important priority because the incidence of this disease is the highest of all congenital diseases involving brain damage which can be preventable with early specific treatment. In recent years, the values of TSH that were considered pathological were modified and the TSH cut-off, the title of hormone to be taken as the limit of significance for determining a subject suffering from CH, has been progressively lowered. In Calabria the introduction of the new value of TSH cut-off on blood spot, has led to a considerable increase in the frequency of CH, particularly in the case of the thyroid in situ normal ultrasound and of the diagnosis of transitional forms of CH.